2010
DOI: 10.1093/jxb/erp379
|View full text |Cite
|
Sign up to set email alerts
|

K+ starvation inhibits water-stress-induced stomatal closure via ethylene synthesis in sunflower plants

Abstract: The effect of water stress on stomatal closure in sunflower plants has been found to be dependent on K(+) nutrient status. When plants with different internal K(+) content were subjected to a water-stress period, stomatal conductance was reduced more markedly in plants with an adequate K(+) supply than in K(+)-starved plants. K(+) starvation promoted the production of ethylene by detached leaves, as well as by the shoot of whole plants. Water stress had no significant effect on this synthesis. The effect on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 43 publications
3
43
0
3
Order By: Relevance
“…Studies in greenhouses and with potted plants have demonstrated the importance of K supply in the resistance of plants to drought. K plays many fundamental physiological and metabolic roles in terrestrial plants in relation to water economy and osmotic homeostasis, such as maintenance of cellular turgor and osmotic pressure (Ashraf et al, 2002;Levi et al, 2011), control of water conductance and transpiration (Harvey & van den Driessche, 1999;Arquero et al, 2006;Benlloch-González et al, 2010), improvement of root hydraulic conductivity (El-Mesbahi et al, 2012), regulation of sap flow (Oddo et al, 2011), regulation of membrane potentials (Schroeder & Fang, 1991), stomatal control (Talbott & Zeiger, 1996;Benlloch-González et al, 2010) and maintenance of ionic homeostasis or transmembrane potential (Su et al, 2001;Waraich et al, 2011). Moreover, field studies have observed that K, apart from its role in stomatal control and water conductance, can further affect water economy as an osmolyte (Babita et al, 2010;Levi et al, 2011) directly linked to improving the capacity to retain water (Nandwal et al, 1998;Rao et al, 2012).…”
Section: Box 1 Main Ecophysiological Roles Of Kmentioning
confidence: 99%
“…Studies in greenhouses and with potted plants have demonstrated the importance of K supply in the resistance of plants to drought. K plays many fundamental physiological and metabolic roles in terrestrial plants in relation to water economy and osmotic homeostasis, such as maintenance of cellular turgor and osmotic pressure (Ashraf et al, 2002;Levi et al, 2011), control of water conductance and transpiration (Harvey & van den Driessche, 1999;Arquero et al, 2006;Benlloch-González et al, 2010), improvement of root hydraulic conductivity (El-Mesbahi et al, 2012), regulation of sap flow (Oddo et al, 2011), regulation of membrane potentials (Schroeder & Fang, 1991), stomatal control (Talbott & Zeiger, 1996;Benlloch-González et al, 2010) and maintenance of ionic homeostasis or transmembrane potential (Su et al, 2001;Waraich et al, 2011). Moreover, field studies have observed that K, apart from its role in stomatal control and water conductance, can further affect water economy as an osmolyte (Babita et al, 2010;Levi et al, 2011) directly linked to improving the capacity to retain water (Nandwal et al, 1998;Rao et al, 2012).…”
Section: Box 1 Main Ecophysiological Roles Of Kmentioning
confidence: 99%
“…Ethylene is known to regulate stomatal movement, but its effect on stomatal movement is contradictory (Acharya and Assmann, 2009;Wilkinson and Davies, 2010). Some studies reveal that ethylene induces stomatal opening and prevents abscisic acid (ABA) -or some stresses -triggered stomatal closure (Levitt et al, 1987;Tanaka et al, 2005Tanaka et al, , 2006Wilkinson and Davies, 2009;Benlloch-Gonz alez et al, 2010), whereas other studies show that it triggers closure (Tissera and Ayres, 1986;Young et al, 2004). Although the stomatal responses to ethylene are well studied, the underlying signal transduction pathways are not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of ethylene in stomatal behaviour has been suggested, its effect in this process seems rather contradictory (Acharya & Assmann 2009;Wilkinson & Davies 2010). In some species, ethylene induces stomatal opening and/or inhibits ABA-induced stomatal closure, or induces stomatal sensitivity to stresses/cues in which ABA is the normal signal for the given stomatal response (Madhavan et al 1983;Levitt et al 1987;Merritt et al 2001;Mills et al 2009;Benlloch-Gonza´lez et al 2010), whereas in other species it induces closure (Pallas & Kays 1982;Giulivo 1986;Tissera & Ayres 1986;Gunderson & Taylor 1991;Young et al 2004;Desikan et al 2006;He et al 2011).…”
Section: Introductionmentioning
confidence: 99%